PERSEPSI MASYARAKAT TERHADAP PELAKSANAAN KEBIJAKAN PERATURAN DAERAH (PERDA) KABUPATEN POLEWALI MANDAR TENTANG KAWASAN TANPA ROKOK - HASANUDDIN; ANDI ISMAWATY (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
This study aims to determine public perception of the policy of regional regulations, Polewali Mandar Regency, regarding non-smoking areas. This research is a descriptive analysis based on quantitative research using language (verbal) to provide general conclusions. The data acquisition techniques used are direct observation of the field and intensive interviews by asking questions that are directly related to the research topic. The data analysis is carried out in a display in which data is presented in the form of a matrix and data is reduced. The results showed that the dominant community spoke well and agreed on the existence of this regulation. Based on the determination of the non-smoking area, the imposition of administrative sanctions and the consent to the determination of the regional regulation (Perda), No. 4 of 2015 in relation to areas without smoking, so that this regulation can be implemented.